Regional Disparity and Social-Economic Convergence in New Autonomous Regions in Banten Province - Amalia, Fitri; Fitrijanto, Arief (Department of Urban and Regional Planning, Universitas Diponegoro, 2022)
As a new province after separating from West Java province, Banten province has experienced various economic growth among its regions, which can reveal disparity in development. Some regions have abundant resources, productive human resources, and access to good economic activities, while others do not. This condition causes inequality between regions. Regional convergence analysis measures not only economic variables but also social measures, such as the Human Development Index (HDI), poverty, and unemployment. This study aims to analyze sigma and absolute beta convergence, in addition to measuring the speed of the new autonomous region (Daerah Otonom Baru/DOB) economic growth convergence in Banten. The study method for regional disparity uses coefficient of variation and klassen typology. The klassen typology approach was used to identify sectors. The results of this study show that disparities occur in regions/cities within the province. The GDRP per capita, HDI, poverty, and unemployment in each region from years 2015-2019 were analyzed using the analytical methods σ-convergence and β-convergence. Regional convergence also occurs, but it is not clear enough to show the possible rate distribution convergence in the future. Socioeconomic factors, including unemployment and poverty, have become factors that impact the rate convergence in the province. Meanwhile, the human resource quality factor does not significantly impact. The new autonomous region (DOB) strategy uses a developing regional strategy, while the parent region has a lagging status. The implication of this research is that each region needs to develop sectors according to its characteristics.